Thermogravimetric Characteristics and Non-isothermal Kinetics of Macro-Algae With an Emphasis on the Possible Partial Gasification at Higher Temperatures - Ali, Imtiaz; Bahadar, Ali (Frontiers in Energy Research, 2019)
Pyrolysis of Turbinaria ornata was realised in a thermogravimetric analyzer. The process was crudely classified into primary and secondary reaction zones. In the primary reaction zone, the thermal decompositions of the low-thermal stable components produced volatiles and biochar. The solid products obtained from the primary decomposition reactions contained inorganics with heavy metals. At mild-to-high temperatures, the catalytic effects accompanied gasification using oxygen, which was partially supplied by the oxygen carriers present in the solids and evolved gases. In order to study the pyrolytic conversion, combined and multiple reaction schemes were employed. While the model-free methods helped to provide the accurate activation energies and the initial value of the pre-exponential factor, the non-linear regression optimized the chosen model parameters. In this study, a simple order-based model was compared with the versatile Šesták-Berggren (SB) model considering combined and multiple reactions. The application of a multiple reaction scheme to the primary and secondary reaction zones concluded that a simple order-based model suffices for the kinetic analysis. The secondary decomposition was shown to start with a high activation energy, which decreased appreciably when the conversion proceeded towards completion.